(untitled) (PerCursos, 2022)
The article proposes a dialogue with Milton Santos’ theory based on the idea, elaborated by the present author, of survival technology as a combination of ancestral knowledge, know-how, technique and technology for the daily construction of the urban periphery. Understood as an opaque space, the periphery is at once a roughness, a resistance, and an actualization of the selective modernization of urban space. It is suggested, from this, that surviving in these places requires an alternative rationality for its daily construction. Based on the land occupation called Cidade Locomotiva, built in the city of Ribeirão Preto in the countryside of the state of São Paulo, it was examined how the population that resides there has built and keeps building this place through the survival technology. The methodology applied was a bibliographic review, consulting the secondary data source and access to primary data through technical interviews with the local government, the leaders and residents of the occupation, in addition to fieldwork during the period of two years. This paper seeks to demonstrate the knowledge that this population holds regarding these vectors of modernization and the limits they impose on their daily lives. Thus, the purpose is to understand how the survival technology, as an alternative modernity constituted in the daily life of the place, acts as a resistance, even if it reproduces certain practices, to the Brazilian corporate urbanization.